Controlled synthesis and Raman study of a 2D antiferromagnetic P-type semiconductor: α-MnSe. Issue 14 (7th April 2021) - Li, Ningning; Zhu, Leilei; Shang, Honghui; Wang, Feng; Zhang, Yu; Yao, Yuyu; Wang, Junjun; Zhan, Xueying; Wang, Fengmei; He, Jun; Wang, Zhenxing
Abstract : The controlled synthesis of 2D antiferromagnetic α-MnSe single crystals with different growth orientations is realized via the atmospheric chemical vapor deposition (APCVD) method. The Raman study related to the magnetic transition is demonstrated. Abstract : Two-dimensional (2D) non-van der Waals magnetic materials have attracted considerable attention due to their high-temperature ferromagnetism, active surface/interface properties originating from dangling bonds, and good stability under ambient conditions. Here, we demonstrate the controlled synthesis and systematic Raman investigation of ultrathin non-van der Waals antiferromagnetic α-MnSe single crystals. Square and triangular nanosheets with different growth orientations can be achieved by introducing different precursors via the atmospheric chemical vapor deposition (APCVD) method. The temperature-dependent resonant enhancement in the Raman intensity of two peaks at 233.8 cm −1 and 459.9 cm −1 gives obvious evidence that the antiferromagnetic spin-ordering is below T N ∼ 160 K. Besides, a new peak located at 254.2 cm −1, gradually appearing as the temperature decreased from 180 K to 100 K, may also be a signature of phase transition from paramagnetic to antiferromagnetic. The phonon dispersion spectra of α-MnSe simulated by density functional perturbation theory (DFPT) match well with the observed Raman signals. Moreover, a fabricated α-MnSe phototransistor exhibits p-type conducting behavior and high photodetection performance. We believe that these findings will be beneficial for the applications of 2D α-MnSe in magnetic and semiconducting fields.